Baksos Kesehatan Penduduk Pralansia & Lansia dengan Hipertensi di Rw 01 Kelurahan Tanjungrejo Kecamatan Sukun Kota Malang - Hilda Mazarina Devi; Ronasari Mahaji Putri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The results of a preliminary study at RT 06 RW 01 Tanjungrejo Village, Sukun District, Malang City found that 25 elderly people experience hypertension and the number of elderly people with hypertension reached 89.28% of the entire elderly population living in this area. Social service activities are carried out in the form of a series of activities: health education through poster media with the topic